Tear antibodies to SARS‐CoV‐2: implications for transmission. Issue 11 (1st November 2021) - Selva, Kevin J; Davis, Samantha K; Haycroft, Ebene R; Lee, Wen Shi; Lopez, Ester; Reynaldi, Arnold; Davenport, Miles P; Kent, Helen E; Juno, Jennifer A; Chung, Amy W; Kent, Stephen J
Abstract: Objectives: SARS‐CoV‐2 can be transmitted by aerosols, and the ocular surface may be an important route of transmission. Little is known about protective antibody responses to SARS‐CoV‐2 in tears after infection or vaccination. We analysed the SARS‐CoV‐2‐specific IgG and IgA responses in human tears after either COVID‐19 infection or vaccination. Methods: We measured the antibody responses in 16 subjects with COVID‐19 infection for an average of 7 months before, and 15 subjects before and 2 weeks post‐Comirnaty (Pfizer‐BioNtech) vaccination. Plasma, saliva and basal tears were collected. Eleven pre‐pandemic individuals were included as healthy controls. Results: IgG antibodies to spike and nucleoprotein were detected in tears, saliva and plasma from subjects with prior SARS‐CoV‐2 infection in comparison with uninfected controls. While receptor‐binding domain (RBD)‐specific antibodies were detected in plasma, minimal RBD‐specific antibodies were detected in tears and saliva. By contrast, high levels of IgG antibodies to spike and RBD, but not nucleoprotein, were induced in tears, saliva and plasma of subjects receiving 2 doses of the Comirnaty vaccine. Increased levels of IgA1 and IgA2 antibodies to SARS‐CoV‐2 antigens were detected in plasma following infection or vaccination but were unchanged in tears and saliva. Comirnaty vaccination induced high neutralising Abs in the plasma, but limited neutralising antibodies were detected in saliva or tears. Conclusion: Both infection and vaccination induce SARS‐CoV‐2‐specific IgG antibodies in tears. RBD‐specific IgG antibodies in tears were induced by vaccination but were not present 7 months post‐infection. This suggests the neutralising antibodies may be low in the tears late following infection. Abstract : The ocular surface may be an important route of SARS‐CoV‐2 transmission. We found SARS‐CoV‐2‐specific antibodies in tears, saliva and plasma from participants either convalescent from COVID‐19 or receiving the Pfizer Comirnaty vaccine.